Civil aviation and tourism demand in Montenegro: A panel data approach - Iva Bulatovic; Andreas Papatheodorou (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: The purpose of the paper is to investigate the role of civil aviation in the case of Montenegro, one of the smallest countries in Europe and one whose economy heavily relies on tourism. Methods: For this research, a dynamic panel data approach is used, where five models are proposed for modelling tourism demand. Available seats per kilometer, the Herfindahl-Hirschman index, jet fuel prices, exchange rates, and seasonality are used as the models' explanatory variables, in line with the available litetrature. Results: The econometric results show that all suggested models are valid, the explanatory variables are statistically significant, and their coefficients have the expected sign, suggesting a strong relationship between tourism demand and civil aviation. Implications: Apart from being one of the first attempts to highlight the civil aviation and tourism nexus in the context of Montenegro, this paper contributes to the literature by suggesting a way forward for destination managers and policymakers in small countries with great tourism potential.
Keywords: L83; C23; C1; 330; tourism demand; aviation; panel data